2008
DOI: 10.1016/j.jhydrol.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy fluxes and vegetation-atmosphere parameters in irrigated and natural ecosystems of semi-arid Brazil

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0
40

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(182 citation statements)
references
References 43 publications
(52 reference statements)
11
131
0
40
Order By: Relevance
“…Os resultados para o albedo planetário e temperatura de brilho foram corrigidas atmosfericamente para obtenção do albedo (α 0 ) e temperatura (T 0 ) da superfície através de equações de regressão obtidas de medições simultâneas em campo e por sensoriamento remoto na região semiárida brasileira (TEIXEIRA et al, 2008;TEIXEIRA et al, 2009a;TEIXEIRA, 2010;TEI-XEIRA et al, 2014).…”
Section: Modelagem Da Produtividade Da áGuaunclassified
See 2 more Smart Citations
“…Os resultados para o albedo planetário e temperatura de brilho foram corrigidas atmosfericamente para obtenção do albedo (α 0 ) e temperatura (T 0 ) da superfície através de equações de regressão obtidas de medições simultâneas em campo e por sensoriamento remoto na região semiárida brasileira (TEIXEIRA et al, 2008;TEIXEIRA et al, 2009a;TEIXEIRA, 2010;TEI-XEIRA et al, 2014).…”
Section: Modelagem Da Produtividade Da áGuaunclassified
“…onde o coeficiente a L foi espacialmente distribuído através de sua relação com T a (TEIXEIRA et al, 2008).…”
Section: Modelagem Da Produtividade Da áGuaunclassified
See 1 more Smart Citation
“…An alternative would be a relationship between the R n /R g ratio and IAF or multilinear regression models including IAF in their formulation. The R n /R g ratio and R n,l have been reported for several crops and types of vegetation (Fontana et al, 1991;Souza and Escobedo, 1997;Souza et al, 2010;Teixeira, 2001;Teixeira et al, 2008;Zhang et al, 2010), from which different relationships can be found. For instance, Souza and Escobedo (1997) found an inverse relationship between R n /R s and LAI for bean crop, Teixeira (2001) reported a direct linear relationship whereas no relation was found by Fontana et al (1991) for a soybean crop under soil totally covered.…”
Section: Resultsmentioning
confidence: 99%
“…O método BERB tem sido aplicado frequentemente em várias culturas, tais como: abacaxi (Souza et al, 2008), milho (Steduto & Hsiao, 1998), feijão caupi (Lima et al, 2005), videira (Teixeira et al, 2007), forrageira (Silva et al, 2005), bananeira (Teixeira, 2001) e café (Righi et al, 2007). Dentre as vantagens desta técnica se destacam sua simplicidade, baixo custo e o fato de apresentar bons resultados quando comparados aos métodos dos vórtices turbulentos e lisimétrico (Gavilán & Berengena, 2007;Silva et al, 2005;Todd et al, 2000), tal como desempenho superior ao método aerodinâmico (Molder et al, 1999).…”
Section: Introductionunclassified